2003
DOI: 10.1021/jp0223760
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of the Butene Isomers in Faujasite: A Combined ab-Initio Theoretical and Experimental Study

Abstract: The adsorption behavior of the butene isomers on NaY zeolite is studied experimentally and compared with quantum chemical predictions. The adsorption experiments were carried out with the pulse chromatographic method, the calculations were performed both on the HF as on the DFT-B3LYP level in combination with the 6-31G* and the 6-311+G** basis set. The results of the calculations are in line with the experimental ones for the cation-butene isomer interaction in the gas phase; the same adsorption trend in the z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 48 publications
2
47
1
Order By: Relevance
“…Either a cluster based model may be used in which part of the zeolite is cut out from the periodic structure or a periodic model in which the material is simulated using periodic boundary conditions. [273][274][275][276][277][278] In most cases, not all atoms are described at the same level of theory and a layered approach is used in which part of the system is described very accurately and the rest is described at a lower level of theory. 271,272 The periodic model is in principle the most natural way to simulate the molecular environment but also comes at a serious computational cost.…”
Section: View Article Onlinementioning
confidence: 99%
“…Either a cluster based model may be used in which part of the zeolite is cut out from the periodic structure or a periodic model in which the material is simulated using periodic boundary conditions. [273][274][275][276][277][278] In most cases, not all atoms are described at the same level of theory and a layered approach is used in which part of the system is described very accurately and the rest is described at a lower level of theory. 271,272 The periodic model is in principle the most natural way to simulate the molecular environment but also comes at a serious computational cost.…”
Section: View Article Onlinementioning
confidence: 99%
“…In the case of the adsorption of diatomic molecules on cationic zeolites, such as CO [21] and N 2 [22,23] but also concerning the adsorption of nitriles, end-on s-bonding interactions only are usually considered. In contrast, for olefins such as butenes [24,25] and pentenes [26] side-on pbonding is very likely to occur.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, experimental investigations in molecular details of structures and adsorption dynamics and interaction energies of hydrocarbons in zeolites have been reported [12][13][14][15][16][17][18]. It was found that the pore size of zeolites had strong effects on the geometries of adsorption sites, the structures of the adsorption complexes, and the adsorption energies.…”
Section: Introductionmentioning
confidence: 99%